2022
DOI: 10.1002/cctc.202200557
|View full text |Cite
|
Sign up to set email alerts
|

Acid and Base Water Coexists in a Micro‐Structured Ionic Liquid and Catalyzes Organic Reactions in One‐Pot

Abstract: The most paradigmatic example of antagonist chemical species are protons and hydroxyls, and their coexistence in a liquid system is of high interest. Here we show that commercial ionic liquids stabilize microdroplets of water with pH<0 and pH>14, concomitantly and without any additive, and that this micro‐structured liquid medium catalyzes organic reactions in one‐pot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“… [31] In order to obtain the enyne compounds in a more sustainable and reusable system, we have performed the cascade reaction in ionic liquids. In our group, we have previously optimized other catalytic reactions in ionic liquids,[ 32 , 33 ] including cascade processes. [33] Here, we tested different ionic liquids, and it was found that [bmim][PF 6 ], [bmim][BF 4 ] and [bmim][OTf] are all suitable for the reaction, to give yields of 3 a >90 % (Figure S7).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… [31] In order to obtain the enyne compounds in a more sustainable and reusable system, we have performed the cascade reaction in ionic liquids. In our group, we have previously optimized other catalytic reactions in ionic liquids,[ 32 , 33 ] including cascade processes. [33] Here, we tested different ionic liquids, and it was found that [bmim][PF 6 ], [bmim][BF 4 ] and [bmim][OTf] are all suitable for the reaction, to give yields of 3 a >90 % (Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…In our group, we have previously optimized other catalytic reactions in ionic liquids,[ 32 , 33 ] including cascade processes. [33] Here, we tested different ionic liquids, and it was found that [bmim][PF 6 ], [bmim][BF 4 ] and [bmim][OTf] are all suitable for the reaction, to give yields of 3 a >90 % (Figure S7). The ionic liquids with Cl − as a counteranion (entries 3 and 6 in Figure S7) where discarded because they formed the Cl‐substituted Sonogashira intermediate, after substitution of the Br by the Cl atom, hampering the elimination step.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the possibility of using the advantages of spatially localized reactions in media structured due to reagent-solvent interactions was reported, which opened new ways of developing chemistry in ordered liquids. [19][20][21] Seminal studies by A. Khlobystov, [22][23][24] C. Li, [25][26][27] L. Li, [28][29][30] and A. Corma [31][32][33] and their coworkers have shown the power of connecting molecular transformations and supramolecular/nanoscale properties of the environment. The transition from molecular to nanoand microscale in the study of chemical reactions in liquid media requires the use of specially designed experimental approaches.…”
Section: Introductionmentioning
confidence: 99%